Power Contestation on Marriage Age Discourse in dealing with Islamic Values: A Case Study on Nahdlatul Ulama - Dian Eka Rahmawati; Muhadjir Darwin; Munawar Ahmad (Jurnal Studi Pemerintahan, 2018)
This study aims to understand the debate on the issue of early prevention from the perspective of NU and NU women activist group. Why there is a difference between NU structures and NU women activist groups. What the knowledge regime that underlies the legitimacy of their attitude is. What are the interests behind differences in attitudes and knowledge regimes used. This study uses a qualitative method. The data was collected by interviewing the board of Muslimat NU, PP Fatayat NU, and PP Rahima and collecting documentation from books, journals, magazines, printed and online newspapers, official website, and mass media decisions. Data analysis techniques performed with data reduction, data display, and conclusion. The result shows that differences in attitudes about the issue of early marriage between NU structures and NU women activist groups stem from different perspectives and interests. Differences perspectives can be seen from differences in interpretation "baligh" as the basis for setting marriage age limit. The interest of the NU structures to accomodate early marriage practices are still prevalent among NU and maintain the status quo of the NU gender habitus. The interest of NU women activist groups is to contextually interpret fikih and to fight for the ideology of theological feminism prosecuting patriarchy within the NU gender habitus. NU Women’s activist groups can reproduce reason about gender relation in Islam that derived from the accumulation of social capital and cultural capital. Although it cannot change the NU's patriarchal gender habitus, the reproduction of reason by NU women activist groups is able to present itself as an alternative gender discourse within NU.